2021
DOI: 10.3390/rs13173420
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Daily Evapotranspiration at Field Scale Using the Harmonized Landsat and Sentinel-2 Dataset, with Sharpened VIIRS as a Sentinel-2 Thermal Proxy

Abstract: Accurate and frequent monitoring of evapotranspiration (ET) at sub-field scales can provide valuable information for agricultural water management, quantifying crop water use and stress toward the goal of increasing crop water use efficiency and production. Using land-surface temperature (LST) data retrieved from Landsat thermal infrared (TIR) imagery, along with surface reflectance data describing albedo and vegetation cover fraction, surface energy balance models can generate ET maps down to a 30 m spatial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 96 publications
1
22
0
Order By: Relevance
“…Previous studies (Knipper et al 2019b ; Semmens et al 2016 ) focusing on these regions have demonstrated that the 16-day revisit of Landsat 8 was not enough to capture the vineyard response to stress. Other studies showed Landsat sampling was even more insufficient for crops like alfalfa which have higher ET temporal dynamics due to monthly cuttings, and pose a significant challenge to ET modeling (Anderson et al 2021 ; Xue et al 2021 ).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies (Knipper et al 2019b ; Semmens et al 2016 ) focusing on these regions have demonstrated that the 16-day revisit of Landsat 8 was not enough to capture the vineyard response to stress. Other studies showed Landsat sampling was even more insufficient for crops like alfalfa which have higher ET temporal dynamics due to monthly cuttings, and pose a significant challenge to ET modeling (Anderson et al 2021 ; Xue et al 2021 ).…”
Section: Study Areamentioning
confidence: 99%
“…Model results are compared to flux measurements from EC systems as observed, and with a correction for energy balance closure error, which is reported on the order of 10–30% (Allen et al 2011 ). Following previous studies (Anderson et al 2021 ; Xue et al 2021 ), a residual correction approach was used at most sites, assigning the energy budget residual to the daily latent heat flux. At SLM001 and SLM002, a modified residual correction was used to minimize impacts of nighttime shifts in wind patterns from off-field (Anderson et al, 2018 ).…”
Section: Data and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the continuous development of remote sensing (RS) technology in recent decades [7][8][9], satellite sensors with multiple spatial, temporal, and spectral resolutions (e.g., Land Remote Sensing Satellite (Landsat), Moderate Resolution Imaging Spectroradiometer (MODIS), Advanced Very-High-Resolution Radiometer (AVHRR), and Sentinel) have become ideal tools for estimating ET at a regional scale [10][11][12][13]. Various models have been reported for estimating ET with RS datasets [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, algorithms for correcting biased ET estimations caused by land surface heterogeneity have mainly focused on the temperature downscaling method [2,46,47]. By obtaining high-resolution ET, the mixed pixels in low-resolution data are reduced, and the influence of the heterogeneous surface on ET is reduced [44].…”
Section: Introductionmentioning
confidence: 99%